Gender Type as a Moderator Variable in the Relationship between Teacher’s Job Satisfaction and Professional Motivation using Multi-group Structural Equation Modeling - Abdel- Haleim, Reda Rabie (Journal of Educational and Psychological Sciences, 2020)
The current research aims at identifying the level of job satisfaction and professional motivation in teachers, as well as the examination of the role of their gender as a moderator variable in that relationship using a multi-group structural equation modeling (SEM). The sample consisted of (221) teachers from Minia Governorate, Egypt. For data collection, the researcher prepared two scales; the job satisfaction scale and the professional motivation scale and applied them on the study sample after obtaining the approval of the local ethical committee. Results revealed that all job satisfaction dimensions and the overall degree of job satisfaction were within a moderate possession degree. Furthermore, the study results demonstrated that the moderating role of the gender male- female did not differ in the relationship between job satisfaction and professional motivation of teachers. In light of the research results, a set of recommendations and proposals presented aimed at increasing the level of job satisfaction and improving the professional motivation of teachers.
Keywords: job satisfaction; professional motivation; teachers- structural equation modeling